Development of Website BEM FEBTD Universitas Nahdlatul Ulama Surabaya - Ahmad Muthoharun; Rizqi Putri Nourma Budiarti (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
Currently BEM FEBTD UNUSA does not yet have a web-based information system, and only relies on delivering information and documentation through social media, namely Instagram. The drawback is that the management cannot manage the schedule so that information on the progress of each work program is obtained. This causes limited information that can be known by the academic community about work programs from year to year. Therefore, media is needed that can manage the work program of BEM FEBTD UNUSA. The methodological stages used are problem identification, website needs analysis, website design, website creation, website testing, and website testing analysis. The results of this study are the formation of the BEM FEBTD UNUSA website, and the administrators can manage work program schedules well, provide activity information, organizational profiles, facilitate various news search purposes, important information announcements, and activity documentation galleries. Testing is done by Black Box Testing and Usability Testing. The success percentage of Black Box Testing with 117 Test Cases is 100%. Meanwhile, the test results from Usability Testing show that according to the admin and supervisor, they strongly agree if the website is easy to use, fast, memorable, no errors are found, and satisfied when used. Meanwhile, according to administrators and visitors, they agree that if the website is easy to use, fast, memorable, no errors are found, and satisfied when used.